A meditative enquiry into presence: Unmaking the autoethnographic self. (1st September 2021) - Stephens, Tim
The article consists of two parts, Introduction and/or Conclusion and a Meditative Enquiry, to be read in any order, if indeed we do 'read' meditative enquiry. Meditative enquiry here concerns the meditative writing and/or reading of this article on presence. The enquiry is divided into numerous subheadings that encourage a slow and circular, rather than linear, narrative, and a participative reading approach, in which each section aims to return to, or arrive in, the present moment. The materiality of our presence is continuous, whether or not we are conscious of being in the present. The article also enacts resistance to, or an apparent inability of conscious awareness to arrive in, and stay with, what is happening in this moment. Implications are, firstly, the unmaking of: a qualitative researcher-participant's 'Self'; and the autoethnographic self within writing as creative practice. Secondly, validating a dual contribution of meditation to philosophy and writing on presence.